"Bunuh Diri" Yesus: Memaknai Ulang Peristiwa Paskah Kristiani - Kayangan Kayangan; Meisyel Liku Allo (Melo: Jurnal Studi Agama-agama, 2022)
These writings focus on Christ’s work of redemption through his “suicide”. The lack of application of Jesus works is a problem for Christians. The work of Jesus on the cross was the central part of all Christian beliefs that were celebrated as the Passover. Passover was lived as or has been redeemed by men form the condemnation of sin. The study used a qualitative approach and study library. The result is that Jesus was basically “suicide” but not for Himself but for man. Mindful of the consequences of impending death, He sacrificed himself for humans. The purpose of this study is to show our readers that the feeling of Christian Passover is Jesus work in an effort to release humans from punishment for sin. Keywords: “Suicide”; Passover; Salvation; Human